Evaluation of the impact of two educational interventions on GP management of familial breast/ovarian cancer cases: a cluster randomised controlled trial. - Watson, E; Clements, A; Yudkin, P; Rose, P; Bukach, C; Mackay, J; Lucassen, A; Austoker, J (2001)
BACKGROUND: It has been suggested that primary care should become more involved in providing genetic services, such as basic risk assessment, to enable patients with a moderate/high risk to be referred and those with a low risk to receive reassurance and advice from their general practitioner (GP). However, GPs currently lack knowledge and confidence in this area. AIM: To investigate the effect of an in-practice educational session and information pack on GP management of familial breast/ovarian cancer cases. DESIGN OF STUDY: Cluster randomised controlled trial. SETTING: GP principals in 170 practices in Oxfordshire and Northamptonshire. Of the 688 GPs, 426 (62%) participated. METHOD: Practices were randomised either to Group A (receiving an inpractice educational session plus information pack), Group B (receiving an information pack alone), or Group C (receiving neither an educational session nor a pack). The main study outcome was the proportion of GPs making the correct referral decision on at least five out of six family history vignettes. A secondary outcome was GPs' reported confidence in managing patients with a family history of breast/ovarian cancer, measured by a score that was generated by combining responses to four questions. RESULTS: There was a 40% (95% CI = 30-50%, P < 0.001) improvement in the proportion of GPs who made the correct referral decision on at least five out of the six vignettes in Group A (111/140 [79%]) compared with Group C (controls) (63/162 [39%]), and a 42% (95% CI = 31-52%, P < 0.001) improvement in Group B (100/124 [81%]) compared with the control group. There was a trend in reported confidence in the management of individuals with a family history of breast/ovarian cancer from a mean confidence score of 2.3 in Group A to 2.0 in Group B and 1.5 in Group C (P < 0.001). CONCLUSION: Providing GPs with an information pack significantly improved referral decisions regarding patients with a family history of breast/ovarian cancer. Although extremely well received, an in-house educational session produced no additional improvements. There were, however, greater levels of reported confidence in the group who received the educational session in addition to the information pack.